The Change of Wood Acidity during Drying Process - Deded S Nawawi; Trisna Priadi; Benny Murwentiano (Jurnal Ilmu dan Teknologi Kayu Tropis, 2012)
Wood acidity is an importance factors in the wood processing and utilization. The acidity of wood might change due to some factors such as moisture, drying, and storage time of wood. The wood acidity of two wood species; sengon (Paraserianthes falcataria) and manii (Maesopsis eminii) and its change by drying process were investigated with respect to pH value and buffering capacity. Drying of wood was carried out on 28 and 60 oC for 24, 48, 72 and 144 h, respectively. The drying of wood was able to change of wood acidity. The acidity of wood increased by increasing the drying temperature and time. On the temperature of 60 oC, a lower pH value and higher bufering capacity of wood were obtained for longer time of drying. Manii wood was more acidic than that of sengon wood.Key words: bufering capacity, pH value, wood acidity, wood drying